2009
DOI: 10.1055/s-0028-1109469
|View full text |Cite
|
Sign up to set email alerts
|

Identifikation von Personen mit familiärem oder hereditärem Darmkrebsrisiko mittels eines Fragebogens zur Familienanamnese

Abstract: If the questionnaire is used on a population-based level and the participation rate is 35 %, approximately 542 000 persons in the age group 30 - 49 years (816 000 in the age group 30 - 54 years) will be classified as having a familial or hereditary risk for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Taking this questionnaire as a basis, Katalinic et al . found a prevalence of 8.2% of persons at increased risk in Germany in the age group of 30–54 years and 6.7% in the age group of 30–49 years respectively (Katalinic et al . 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Taking this questionnaire as a basis, Katalinic et al . found a prevalence of 8.2% of persons at increased risk in Germany in the age group of 30–54 years and 6.7% in the age group of 30–49 years respectively (Katalinic et al . 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The simple three-question instrument about family history of CRC was developed to screen for individuals with an increased risk for familial or hereditary CRC. Taking this questionnaire as a basis, Katalinic et al found a prevalence of 8.2% of persons at increased risk in Germany in the age group of 30-54 years and 6.7% in the age group of 30-49 years respectively (Katalinic et al 2009). In our study, at t1, the prevalence of increased risk was 16% in both age groups and therefore highly increased compared with the German general population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations